Electrical power systems quality - Dugan, Roger C.; Dugan, Roger C. (New York : McGraw-Hill, 2012)
A guide to identifying and preventing the causes of power quality problems. This resource addresses the essentials of power quality and tested methods used to improve compatibility among the power systems, customer equipment, and processes.--[Source inconnue].
1. Introduction -- 2. Terms and definitions -- 3. Voltage sags and interruptions -- 4. Transient overvoltages -- 5. Fundamentals of harmonics -- 6. Applied harmonics -- 7. Long-duration voltage variations -- 8. Power quality benchmarking -- 9. Distributed generation and power quality -- 10. Wiring and grounding -- 11. Power quality monitoring.
{u2164}. r. de: Electrical power systems quality / Roger C. Dugan et al. c2003.
Bibliogr.
Buku bacaan asas fakulti
Publiaussi en version ectronique.
Keywords: Reseaux electriques (Energie) -- Stabilite; Reseaux electriques (Energie) -- Qualite -- Controle; Centrales electriques -- Qualite -- Controle